2020
DOI: 10.1142/s0218495820500089
|View full text |Cite
|
Sign up to set email alerts
|

Market(ing) Wisdom Differences between Family and Non-Family Firms: An Empirical Study on Small and Medium Enterprises

Abstract: In today’s competitive business environment, family and non-family small and medium enterprises (SMEs) strive to survive despite many challenges. Market knowledge and marketing efforts are crucial for them to sustain and enhance business with limited resources. In this paper, we examined three constructs (i) market orientation, (ii) marketing capabilities and (iii) marketing practices impact on the SMEs’ service sector performance. The interaction effect of ownership type (family and non-family firms) was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 162 publications
1
4
0
Order By: Relevance
“…In this sense, MO reflects the organisation’s climate and is regarded as one of the most effective behavioural trend in creating superior value to customers (Andreou et al , 2020; Day, 1994; Gupta et al , 2018; Slater and Narver, 1998). In fact, previous research has found a positive link between MO and performance (Acikdilli et al , 2020; Ghouri et al , 2020; Jaworski and Kohli, 1993; Narver and Slater, 1990), which is in line with the results found by several meta-analyses dealing with this relationship (Ellis, 2006; Shoham et al , 2005). Nonetheless, Shoham et al (2005) alert that the relationship could be stronger if indirect paths are considered.…”
Section: Conceptual Overview and Hypotheses Developmentsupporting
confidence: 90%
See 1 more Smart Citation
“…In this sense, MO reflects the organisation’s climate and is regarded as one of the most effective behavioural trend in creating superior value to customers (Andreou et al , 2020; Day, 1994; Gupta et al , 2018; Slater and Narver, 1998). In fact, previous research has found a positive link between MO and performance (Acikdilli et al , 2020; Ghouri et al , 2020; Jaworski and Kohli, 1993; Narver and Slater, 1990), which is in line with the results found by several meta-analyses dealing with this relationship (Ellis, 2006; Shoham et al , 2005). Nonetheless, Shoham et al (2005) alert that the relationship could be stronger if indirect paths are considered.…”
Section: Conceptual Overview and Hypotheses Developmentsupporting
confidence: 90%
“…The exact way that MO influences firm performance is not consensual. While some authors consider MO to be complementary of other capabilities when impacting performance (Ghouri et al , 2020; Morgan et al , 2009), others consider it to be mediated by marketing capabilities (Asseraf and Shoham, 2019; Kajalo and Lindblom, 2015; Kayabasi and Mtetwa, 2016; Qureshi et al , 2017; Riswanto et al , 2019). This later approach to a mediated relationship between MO and performance was evidenced in Shoham et al (2005), where the authors argued that the effect of MO on performance could be greater if mediated by other capabilities.…”
Section: Conceptual Overview and Hypotheses Developmentmentioning
confidence: 99%
“…All three conditions for reliability and convergent validity are thus met. We tested for heterotraitmonotrait ratio (HTMT) discriminant validity (Ghouri et al 2020;Hair et al 2017) with a threshold value of 0.85, and the constructs are distinct-as shown in Table 5, all ratios are lower than 0.85. Therefore, discriminant validity was also confirmed for each construct.…”
Section: Measurement Modelmentioning
confidence: 99%
“…Research on family businesses has been widespread to include initiatives associated with internationalization (Rexhepi et al, 2017), marketing (Ghouri et al, 2020), technology adoption (Hendayani & Febrianta, 2020), strategic adaptation to the external environment (Duarte Alonso et al, 2018), among other things. Following the extent that family firms contribute to the economy (Bergamaschi & Randerson, 2016;Chahal & Sharma, 2020) and the complexity of supply chains, several reports highlighted critical insights (Jayaram et al, 2014;Maloni et al, 2017;Hendayani & Febrianta, 2020;Darby et al, 2022).…”
mentioning
confidence: 99%
“…Such a characteristic may combine the inherent behavior of SMEs and the perspectives of family businesses. Attempts at exploring this intersection were reported in the literature (e.g., Jayaram et al, 2014;Ghouri et al, 2020;Darby et al, 2022).…”
mentioning
confidence: 99%